The Economy of Communion (EoC) as a New Ideal Economy - Chun, Se-Hak (International Journal of Engineering and Technology, 2018)
The Economy of Communion (EoC) is a business paradigm that has been developed from the praxis of the Focolare Movement to reduce poverty and to disseminate the culture of giving. The EoC business commits to allocating up to two thirds of their profits for the help of people in need. In this regard, this movement is a new market economy philosophy between Marxism and Capitalism. This paper overviews the EoC from the economic perspective, and discusses the sustainability of the EoC business model and introduces cases of the EoC firms.
Keywords: Economy of Communion; Focolare Movement; Business Model; Social Business